KONSEP PEMBINAAN DAN PENGEMBANGAN PROFESIONAL PENDIDIK DAN TENAGA KEPENDIDIKAN - Fitri Yeni; Afriza (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2024)
This research aims to foster and develop professional educators and education personnel. The research method used involves literature study, by collecting and analyzing literature related to this topic. In order to realize the success of education, teachers must become human resources (HR) who are the main development priority. Today's increasingly fierce competition requires tenacity, patience, the ability to anticipate, speed and accuracy in thinking and acting so that you can continue to play an active role in the educational process itself. Educational personnel are employees, namely those who fulfill the requirements specified in the applicable laws and regulations, are appointed by authorized officials and are entrusted with other state duties determined based on the applicable laws and regulations. The development of educational staff can be carried out through training and non-training channels, training channels such as continuing education, upgrading, seminar activities, workshops, etc., non-training channels, for example, can take the form of promotions, giving bonuses and incentives, reprimands and punishments